Economic Impact of 300 KWp PV Rooftop Penetration on Soy Sauce Companies - Muhamad Fahmi Amrillah; Irwan Irwan; Dimas Pratama Yuda (Jurusan Teknik Elektro UIN Sunan Gunung Djati Bandung, 2022)
One of the greatest potentials of renewable energy is solar energy, which can produce electricity. The industry welcomed this to utilize solar energy to produce electricity through a PV rooftop system. The advantage of PV rooftops in producing electrical energy is in terms of investment costs that can eliminate the land component because it utilizes the roof of an industrial building as a place for PV rooftops to produce electrical energy. Soy Sauce companies, as one of the industries engaged in food, can utilize a PV rooftop with 300 kWp to produce electricity. The electrical energy produced by the PV rooftop can reduce 17,23% of the total electrical energy consumed by soy sauce companies in one day from PT. PLN electrical energy sources. A rooftop PV investment capacity of 300 kWp has a payback period of 12 years with an IRR value of 7% and a lifetime of using PV rooftop for 25 years.